PENINGKATAN PRODUKTIVITAS PADI MELALUI PENDEKATAN SEKOLAH LAPANG PENGELOLAAN TANAMAN TERPADU (SLPTT) DI KECAMATAN SESAYAP HILIR KABUPATEN TANA TIDUNG - Sekar Inten Mulyani, dan Elly Jumiati (Universitas 17 Agustus 1945 Samarinda, 2014)
Agricultural sector has important role for supporting region’s food security, especially commodities of rice as staple food of most Indonesian. One of the efforts for increasing food plants, especially rice, which has been done by Agricultural Minister in 2007, is by programming Pengelolaan Tanaman Terpadu (integrated management of plant). It is held by the airy school methods in certain area. An indicator of successful SLPTT can be seen in the increased knowledge, skill and behavior, good cultivation, increased productivity and beyond. For SLPTT area, indicator of ups and downs that are stated by government is about 0,3 ton/ha. This research intends to understand the SLPTT rice in the border areas, rice productivity and increased of rice farmers’ income through SLPTT. This research was held in October – November 2013 to the rice farmers who have become attendants of Sekolah Lapang Pengelolaan Tanaman Terpadu (SLPTT) in sub district Sesayap Hilir, district Tana Tidung. The data collection was questionnaire and direct observation. The proposed hypothesis: There are differences of farmers’ income before and after attending SLPTT rice. SPSS 17 program was used for analyzing the proposed hypothesis by Paired sample t-test. The economical analysis was for counting the income levels by counting the total production cost (TC), acceptance (TR) and income (Π). Before SLPTT, the average of harvest productivity was 893 kg/ha GKP, the average of production cost was Rp 4.323.082,00 and the income was Rp 1.096.917,00. After SLPTT program, the respondents have raised their average productivity to 1.270 kg/ha GKP, production cost is Rp 6.041.463,00 and the average income is Rp 1.687.791,00. The result of paired sample t-test and SPSS is got the significance = 0,000 (sig<0,05). It means, Ho is declined and H1 is accepted. It causes the differences between before and after SLPTT program for rice farmers.